Frequency of Chief Complaints in Patients Referring to Persian Medicine Clinics - Fatemeh Saboktakin; Alireza Yargholi; Fatemeh Moradi; Fatemeh Alizadeh; Mohammad Ali Zareian (Tehran University of Medical Sciences, 2020)
Today, for various reasons, there is a growing tendency towards traditional and complementary medicine in the world as well as growing interest in Persian Medicine in Iran. This study aimed to investigate the frequency of major complaints by patients in some chosen Persian Medicine clinics. In this retrospective cross-sectional study, 1319 files of patients referred to Persian Medicine clinics of Tehran University of Medical Sciences in the fourth week of each month in 2012 were investigated and analyzed in terms of major complaints and demographic indices. Data gathering tool was an information form regulated based on main study goals. Data were analyzed by SPSS software Version 19. mean age of patients was 40.82 ± 16.006 years. The most common complaint in all the clinics was musculoskeletal problems (28,7%). Most of the patients were single housewives (38%). The most common complaints in the single-patient group were musculoskeletal problems (35.44%) and in the married-patient group were skin problems (29.41%). The most common complaints in both genders were musculoskeletal complaints (26% in men &31.44% in women). Due to the prevalence of women referral to Persian Medicine centers, adequate knowledge of gynecological diseases is one of the requirements of Persian Medicine professionals that should be considered in their education. Planning for adequate knowledge of musculoskeletal, digestive, and skin diseases should also be considered in educational curricula.